The Promise of Using Protoplasts in Grapevine Research - Derman, S. S.; Vivier, Melané (South African Journal of Enology and Viticulture, 2022)
Protoplasting refers to the isolation of protoplasts from plant material. These protoplasts are cells bound only by their plasma membranes following the removal of their cell walls. In grapevine research, protoplasting efforts and successes have been reported from 1985 onwards, but recent research has shown a renewed focus on grapevine-derived protoplasts, particularly due to the possibility of using protoplasts in applications such as gene-editing approaches. Grapevine species are generally considered recalcitrant to manipulation in culture and have also proven recalcitrant with regards to protoplasting and particularly in the regeneration of plants from protoplasts. This review will highlight the important milestones in grapevine protoplasting while outlining the current efforts to establish grapevine protoplasting as a routine technique.